WATER-SOAKED SPOT1 Controls Chloroplast Development and Leaf Senescence via Regulating Reactive Oxygen Species Homeostasis in Rice - Xu, Jiangmin; Ji, Zhiyuan; Wang, Chunlian; Xu, Feifei; Wang, Fujun; Zheng, Yuhan; Tang, Yongchao; Wei, Zheng; Zhao, Tianyong; Zhao, Kaijun (Frontiers in Plant Science, 2022)
Transmembrane kinases (TMKs) play important roles in plant growth and auxin signaling. However, its function in regulation of early leaf senescence (ELS) of plants remains unknown. We report here the cloning and functional characterization of the rice WATER-SOAKED SPOT1 gene which encodes a protein belongs to the TMK family and controls chloroplast development and leaf senescence in rice. The water-soaked spot1 (oswss1) mutant displays water-soaked spots which subsequently developed into necrotic symptoms at the tillering stage. The oswss1 exhibits slightly rolled leaves with irregular epidermal cells, decreased chlorophyll contents, and defective stomata and chloroplasts as compared with the wild type. Map-based cloning revealed that OsWSS1 encodes a transmembrane kinase TMK1. Genetic complementary experiments verified that a Leu396Pro amino acid substitution, residing in the highly conserved region of leucine-rich repeat (LRR) domain, was responsible for the phenotypes of oswss1. OsWSS1 was constitutively expressed in all tissues and its encoded protein is localized to the plasma membrane. Mutation of OsWSS1 led to hyper-accumulation of reactive oxygen species (ROS), more severe DNA fragmentation and cell death than that of the wild-type control. In addition, we found that the expression of senescence-associated genes (SAGs) was significantly higher, while the expression of genes associated with chloroplast development and photosynthesis were significantly lower in oswss1 as compared with the wild type. Taken together, our results demonstrated that OsWSS1, a member of TMKs, plays a vital role in the regulation of ROS homeostasis, chloroplast development and leaf senescence in rice.